In situ synthesis of bio-green silver nanoparticles incorporated zeolite a using orthosiphon aristatus leaves extract for antibacterial wound healing - Muhammad Hariz Asraf Hassan, 1992-, author 616347; Nik Ahmad Nizam Nik Malek, 1982-, supervisor 493865; Khairunadwa Jemon, supervisor 601214; Fakulti Sains 8004 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2021)
Thesis (Doktor Falsafah (Biosains)) - Universiti Teknologi Malaysia, 2021